Du nouveau sur la géographie de l’Éthiopie. Poggio Bracciolini, Biondo Flavio et le témoignage de l’ambassade éthiopienne au concile de Ferrare-Florence - Nathalie Bouloux (Afriques)
In August 1441, an embassy of eight monks (four from the Coptic communauty of Cairo, four ethiopans monks from Jerusalem) arrive at the Council of Florence. Two humanists, Poggio Bracciolini and Biondo Flavio, are among the witnesses of the event that they report in their writings. In the fourth book of the De varietate fortunae, Poggio describes a prosperous and exotic Ethiopia, whereas Biondo, by transcribing the questioning of the monks by a commission of cardinals in his Historiarum ab inclinatione Romanorum imperii decades, shows the conflicts between the various representations of Ethiopia and their implications. These texts give evidence of the fascination of some humanists for the far-off lands and of the diverse modes of insertion of Ethiopia in the imago mundi.